2023
DOI: 10.1021/acsami.3c02181
|View full text |Cite
|
Sign up to set email alerts
|

Cathode Interlayer Based on Naphthalene Diimide: A Modification Strategy for Zinc-Oxide-Free Inverted Organic Solar Cells

Abstract: Perylene diimide with ammonium oxide as a terminal group (named PDIN-O) is a well-known cathode interlayer in conventional-type organic solar cells (OSCs). Since naphthalene diimide exhibits a lower LUMO level than perylene diimide, we chose it as a core to further control the LUMO level of the materials. Small molecules (SMs) produce a beneficial interfacial dipole by the end of ionic functionality at the side chain of naphthalene diimide. With the active layer based on a nonfullerene acceptor (PM6:Y6BO), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…HB contains a hexane alkyl chain sandwiched between two electropositive quaternary ammonium and electronegative bromine (Br) pairs. With the strong polarity of ammonium and Br, HB shows a large dipole moment of 10.9 D from amine to Br (Figure c), which might be helpful in forming interfacial dipoles in the device and assisting charge collection. , Additionally, HB possesses a high transmittance from 300 to 900 nm. When HB was dissolved in methanol (MeOH) and cast on a PM6:C5-16 photoactive layer, negligible difference was observed in the absorption spectrum of PM6:C5-16 (Figure d), implying that HB did not alter the morphology of the photoactive layer.…”
Section: Resultsmentioning
confidence: 99%
“…HB contains a hexane alkyl chain sandwiched between two electropositive quaternary ammonium and electronegative bromine (Br) pairs. With the strong polarity of ammonium and Br, HB shows a large dipole moment of 10.9 D from amine to Br (Figure c), which might be helpful in forming interfacial dipoles in the device and assisting charge collection. , Additionally, HB possesses a high transmittance from 300 to 900 nm. When HB was dissolved in methanol (MeOH) and cast on a PM6:C5-16 photoactive layer, negligible difference was observed in the absorption spectrum of PM6:C5-16 (Figure d), implying that HB did not alter the morphology of the photoactive layer.…”
Section: Resultsmentioning
confidence: 99%
“…The values of the align closely with the values. Lower values were observed when PF-NDIN-I-OH was applied in the device, suggesting a potential for leakage current in the device with PF-NDIN-I-OH as the interlayer [ 27 ]. Even though the device with PF-NDIN-I-OH has the lowest values, the device exhibits the best , which mostly contributes to PCE enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…The ionic charges offer polyelectrolytes a straightforward process for a action between molecules and fine-tuning the optical properties [25]. Ad interface properties can be finely tuned by different types of counteranio search has demonstrated that the WF of electrodes and ZnO can be modifi the counteranion [5,[26][27][28]. Polyelectrolytes with various CAs have been u imize the collection of charge capability at the cathode interface [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1–8 In recent years, with the rapid development of active layer materials and interface engineering, the power conversion efficiency (PCE) of single-junction organic solar cells has surpassed 19%. 9–22 However, the lightweight and flexible characteristics of organic solar cells will not be reflected in rigid devices. 23–30 The fabrication of organic solar cells on ultrathin substrates (typically <10 μm in thickness), distinguished by excellent mechanical flexibility and conformable attachment, presents promising applications in the realm of wearable devices.…”
Section: Introductionmentioning
confidence: 99%